Effect of concern about COVID-19 on professional self-efficacy, psychological distress, anxiety, and depression in Peruvian health personnel - Mamani-Benito, Oscar (2021)
ABSTRACT Introduction. Concern about becoming infected with COVID-19 is one of the reactions that has affected the mental health of Peruvian health care workers. Objective. To determine the effect of concern about COVID-19 on professional self-efficacy, psychological distress, anxiety, and depression in health personnel in the Puno region of Peru. Method. An explanatory, cross-sectional study was conducted with the voluntary participation of 401 health workers (such as nurses, physicians, nursing technicians, obstetricians, dentists, psychologists, and nutritionists) of both sexes (24.2% men and 75.5% women) from 12 health networks in the region of Puno, Peru. They were asked to answer the Scale of Concern for the Transmission of COVID-19 in Health Personnel (EPPC-Cov19), Patient Health Questionnarie-2 (PHQ-2, Generalized Anxiety Disorder Scale-2 (GAD-2) and the Professional Self Efficacy Scale (AU-10). Structural Equation Modeling (SEM) was used for data analysis. Results. The factor loads of the explanatory model showed a good fit: χ² (286) = 797.31, p < .001; IFC = .99; RMSEA = .06; SRMR = .07; WRMR = 1.25. Therefore concern about COVID-19 has a greater effect on anxiety (β = .77) and depression (β = .71), as well as psychological distress (β = .65), and only a mild effect on work self-efficacy (β = .12). Discussion and conclusion. Concern about the spread of COVID-19 affects depression, anxiety, psychological distress and work self-efficacy among Peruvian health workers in the Puno region of Peru.